Legal Protection for Nadzir (Waqf Recipient) from Unregistered Waqf Land - Navisa, Fitria Dewi; Fatmawati, Fitri (AL- IKTISAB Journal of Islamic Economic Law, 2021)
Waqf in Indonesia that is carried out by the community is often not by the existing provisions and elements. As a result, there are many problems in waqf. One of the problems that can arise is the existence of waqf land that is not registered. This causes the recipient of the waqf, nadzir, as the manager of the donated land, to often get involved in disputes over the land. For this reason, legal protection and efforts are needed for nadzir from unregistered waqf land. In finding answers to these problems, researchers use certain legal theories as a basis for analyzing them. The method used in this research is normative legal research (normative juridical) and this research is descriptive analysis. The result is, the implementation of waqf in Indonesia is based on Law No. 5 of 1960 concerning Basic Agrarian Regulations (UUPA), Government Regulation No. 28 of 1977 concerning Freehold Land Waqf, Government Regulation No. 24 of 1977 concerning Land Registration, Law No. 41 of 2004 concerning Waqf. These provisions are regulated to ensure certainty and protection for the implementation of waqf. Legal protection of the waqf land is very important considering that many parties want to control the donated land because the land is considered to have high economic value and is a very basic human need. For this reason, in obtaining legal strength and certainty, the waqf land must be registered so that it is legally registered as waqf property by the state. The donated land must obtain a waqf pledge deed which is then made a waqf certificate to ensure legal certainty. If the donated land does not have a waqf certificate, then it does not have legal force.